OVERVIEW OF GROUNDWATER FLOW PREDICTION IN OPEN PIT MINING - nando, kadek nando setiawan; Tedy Agung Cahyadi, (ReTII, 2020)
Dealing with water in open pit mining causes many operational, economic and safety problems. as mining depth increases, hydrogeological conditions become more complex, and water inflow to the mine increases every year, mine water disasters occur frequently, resulting in tens of millions of dollars in economic losses. Therefore, it is necessary to predict the flow of water into the mine. This study aims to determine the groundwater flow model that is suitable for mining, and to see the trend of groundwater flow into the pit and determine the factors that influence the flow of water into the mine. The author conducted comparisons of several literatures to determine the best model, analyze groundwater flow trends and factors that influence water flow to the mine. From these results, it is found that, numerical models provide better results than analytical models, groundwater flow trends increase and decrease and fluctuate, with respect to time and depth, as well as many factors that affect the flow of groundwater to the mine pit, including geology, hydrogeology, and mining activities.